Metal–organic framework-guided growth of Mo2C embedded in mesoporous carbon as a high-performance and stable electrocatalyst for the hydrogen evolution reaction. Issue 41 (6th October 2016) - Qamar, M.; Adam, A.; Merzougui, B.; Helal, A.; Abdulhamid, O.; Siddiqui, M. N.
Abstract : Metal–organic framework is utilized as a confined-template for restrained nucleation and growth of Mo2 C electrocatalyst for highly efficient water splitting. Abstract : Large-scale production of H2 by electrochemical water splitting is discerned as one of the most economical and viable approaches and designing Pt-less electrocatalysts remains at the forefront of this technology development. Herein, in situ transformation of metal–organic frameworks (MOF), impregnated with a molybdenum precursor, into a porous and rigid carbon support and molybdenum carbide (Mo2 C) was demonstrated to fabricate highly active and stable β-Mo2 C/C heterostructure for electrocatalytic H2 evolution. The two-step synthesis approach involved the impregnation of molybdenum source into frameworks of MOF (namely MIL-53(Al)) followed by nucleation and growth of Mo2 C nanocrystals into confined porous texture through carburization. Characterization revealed the formation of mesoporous carbon embodied with crystalline nanoparticles of β-Mo2 C (between 5 and 10 nm). A probable mechanism for the formation of Mo2 C/C nanocomposite is proposed. The propensity of the catalyst was tested towards the electrocatalytic H2 evolution reaction (HER) under alkaline aqueous media (1 M KOH). The electrocatalyst showed a remarkable HER activity as compared to the benchmark electrocatalyst Pt/C and Mo2 C/XC72 black catalysts at 10 mA cm −2 and stability for 20 h at the same current density. Electrochemical impedance spectroscopy results of Mo2 C/C were construed by two time constants, porosity and charge transfer, and the HER reaction followed the Volmer–Heyrovsky mechanism.